2019
DOI: 10.1038/s41598-019-49158-1
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive Spirometric Pattern and Postoperative Pulmonary Complications Following Non-cardiothoracic Surgery

Abstract: Despite a substantial population of patients with a restrictive spirometric pattern, few studies have evaluated postoperative pulmonary complications (PPCs) after non-cardiothoracic surgery in these patients. We conducted a retrospective cohort study of 681 adults with a normal or restrictive spirometric pattern who were referred for preoperative evaluation of PPC risk before non-cardiothoracic surgery between March 2014 and January 2015. Overall, 8.7% (59/681) of study participants developed a PPC following n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Normal spirometry was defined as pre-bronchodilator FEV 1 /FVC ≥ 0.70 and FVC ≥ 80% predicted, and the obstructive spirometric pattern was defined as pre-bronchodilator FEV 1 /FVC < 0.70 irrespective of FVC values 16 . RSP was defined as pre-bronchodilator FEV 1 /FVC ≥ 0.70 and FVC < 80% predicted 1 and was subdivided into mild-to-moderate RSP (60% predicted ≤ FVC < 80% predicted) and severe RSP (FVC < 60% predicted) 17 .…”
Section: Measurementsmentioning
confidence: 99%
“…Normal spirometry was defined as pre-bronchodilator FEV 1 /FVC ≥ 0.70 and FVC ≥ 80% predicted, and the obstructive spirometric pattern was defined as pre-bronchodilator FEV 1 /FVC < 0.70 irrespective of FVC values 16 . RSP was defined as pre-bronchodilator FEV 1 /FVC ≥ 0.70 and FVC < 80% predicted 1 and was subdivided into mild-to-moderate RSP (60% predicted ≤ FVC < 80% predicted) and severe RSP (FVC < 60% predicted) 17 .…”
Section: Measurementsmentioning
confidence: 99%
“…Bartlett et al 9 reported that the correction of the deformity could relieve bronchial obstruction associated with thoracic lordoscoliosis. Furthermore, Shin et al 10 demonstrated a significant association between a restrictive spirometry pattern and postoperative pulmonary complications in patients undergoing noncardiothoracic surgery. Therefore, we decided to perform corrective surgeries in both the cervical and thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…A restrictive ventilatory disorder was defined as FEV 1 /FVC of 70% or higher and FVC less than 0% predicted, and an obstructive ventilatory disorder was defined as FEV 1 /FVC less than 70% 22,23 . The severity of the restrictive ventilatory disorder was further categorized as an FVC of 70% of 80% predicted versus FVC less than 70% predicted because there were too few participants with FVC less than 60% predicted to obtain precise estimates for this group 24 . The severity of the obstructive ventilatory disorder was categorized by FEV 1 (≥80% predicted vs <80% predicted) 23 .…”
Section: Methodsmentioning
confidence: 99%
“…22,23 The severity of the restrictive ventilatory disorder was further categorized as an FVC of 70% of 80% predicted versus FVC less than 70% predicted because there were too few participants with FVC less than 60% predicted to obtain precise estimates for this group. 24 The severity of the obstructive ventilatory disorder was categorized by FEV 1 (!80% predicted vs <80% predicted). 23 Abnormal lung function was defined as having either a restrictive or an obstructive ventilatory disorder.…”
Section: Hong Et Almentioning
confidence: 99%